Compact Dual-Band Circularly Polarized Stacked Patch Antenna for Microwave-Radio-Frequency Identification Multiple-Input-Multiple-Output Application - Enze Zhang; Andrea Michel; Paolo Nepa; Jinghui Qiu (International Journal of Antennas and Propagation)
A compact, low-profile, two-port dual-band circularly polarized (CP) stacked patch antenna for radio-frequency identification (RFID) multiple-input-multiple-output (MIMO) readers is proposed, which employs the shared-aperture technique. The proposed antenna adopts a 1.524 mm thickness Rogers Ro4350b substrate with relative permittivity of 3.48. Two pairs of isolated ports are working at two microwave- (MW-) RFID bands (2.4–2.485 GHz and 5.725–5.875 GHz) with high port isolation of 25 dB and 30 dB, respectively. A shared metal slot layer is designed to separate two feeding structures of the lower band and upper band for port isolation enhancement as well as saving space. Corner-truncated square slot and patch configurations have been designed to obtain CP modes. In the lower and upper MW-RFID bands, the relative impedance bandwidths are 12.2% and 5.7%, and the maximum realized gains are higher than 7.3 dBic. Moreover, two-element configurations have been combined for an RFID MIMO system that occupies a dimension of 119 mm × 119 mm × 12.9 mm. The MIMO antenna performance of envelope correlation coefficient (ECC) is lower than 0.03, and diversity gain is close to 10 dB.